Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1074/jbc.m302444200
|View full text |Cite
|
Sign up to set email alerts
|

α-Melanocyte-stimulating Hormone Inhibits Lipopolysaccharide-induced Tumor Necrosis Factor-α Production in Leukocytes by Modulating Protein Kinase A, p38 Kinase, and Nuclear Factor κB Signaling Pathways

Abstract: The neuropeptide ␣-melanocyte-stimulating hormone (␣-MSH) inhibits inflammation by down-regulating the expression of proinflammatory cytokines such as tumor necrosis factor-␣ (TNF-␣) in leukocytes via stimulation of ␣-MSH cell surface receptors. However, the signaling mechanism of ␣-MSH action has not yet been clearly elucidated. Here, we have investigated signaling pathways by which ␣-MSH inhibits lipopolysaccharide (LPS)-induced TNF-␣ production in leukocytes such as THP-1 cells. We focused on the possible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 49 publications
3
48
4
Order By: Relevance
“…In human diseases, the relationship between concentrations of α-MSH and disease progression in HIV-infection was explored in a prospective study (19). Circulating α-MSH returned to normal levels in patients with sepsis syndrome who recovered and it remained low in those who died (20) As previously reported (23,24), the response to α-MSH was biphasic in inhibitory effects on LPS-induced TNF-α production. One of the possibilities of the reason may be that α-MSH could modulate both inflammatory and antiinflammatory responses regulating intracellular peroxide levels and glutathione peroxidase activity, and an excess dose of α-MSH could break the immunobalance (23).…”
Section: Discussionmentioning
confidence: 63%
“…In human diseases, the relationship between concentrations of α-MSH and disease progression in HIV-infection was explored in a prospective study (19). Circulating α-MSH returned to normal levels in patients with sepsis syndrome who recovered and it remained low in those who died (20) As previously reported (23,24), the response to α-MSH was biphasic in inhibitory effects on LPS-induced TNF-α production. One of the possibilities of the reason may be that α-MSH could modulate both inflammatory and antiinflammatory responses regulating intracellular peroxide levels and glutathione peroxidase activity, and an excess dose of α-MSH could break the immunobalance (23).…”
Section: Discussionmentioning
confidence: 63%
“…The treatment of LPS-stimulated macrophages with α-MSH prevents the translocation of NF-κB from the cytoplasm to the nucleus resulting from a block in IκB degradation (Deng et al, 2004). In addition, the α-MSH-treated macrophages have deactivated p38 (Yoon et al, 2003). These findings suggested that there must be a more proximal inhibition of the LPS-induced intracellular signaling cascade.…”
Section: Discussionmentioning
confidence: 67%
“…The most predominate melanocortin receptor on macrophages and dendritic cells is MC1r (Neumann Andersen et al, 2001), although message for MC3r and MC5r can be detected (Taherzadeh et al, 1999). The engagement of α-MSH with MC1r elevates cAMP levels in the macrophages and activates a cAMP-dependent protein kinase A (PKA; Yoon et al, 2003). The activation of PKA is linked to the inhibition of LPS-activated p38 MAPK and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuropeptide suppresses the pro-inflammatory activity of both innate and adaptive immunity. In macrophages through the melanocortin 1 and 3 receptors, α-MSH suppresses the activation of NF-κB and p38MAP-kinase by IL-1, TNF-α, and endotoxin Manna and Aggarwal, 1998;Taherzadeh et al, 1999;Yoon et al, 2003). The α-MSH suppression of endotoxin mediated inflammation is the result of blocking toll like receptor-4 (TLR4) signaling in macrophages either through suppression of CD14 expression or by translocation of IRAK-M to the endotoxin-engaged TLR4 intracellular complex (Sarkar et al, 2003;Taylor, 2005).…”
Section: Introductionmentioning
confidence: 99%